Implementation of innovative social investments at the local level. Case study - Moroń, Dorota (Research Papers of Wrocław University of Economics, 2018)
The article presents the results of research on the implementation of innovative social investments at the local level based on the case study Assistance from A to Z – Professional activation of homeless people from Wroclaw Circle St. Brother Albert Aid Society. The aim is to analyse the possibilities of applying innovative and investment solutions in the area of social and professional activation of people threatened by social exclusion, especially the homeless. The author uses the case study method and the method of desk research, in which the analysis of the strategy documents, source materials and acts was carried out. The analysis of the Assistance from A to Z project showed that applied in the project forms of support brought satisfactory results in the field of social and professional activation of the homeless, brought social and economic benefits and thus the project can be seen as a social investment
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2018, Nr 510, s. 140-151
Keywords: social innovation; social investments; social activation; professional activation; homelessness; accompaniment method; innowacje społeczne; inwestycje społeczne; aktywizacja społeczna; aktywizacja zawodowa; bezdomność; metoda towarzyszenia